(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
The density of adsorbent bed significantly contributed to solar cooling performance (COP). The density determines how well the heat and mass transfer are. Besides that, the COP is also determined by ambient temperature. This research aims to investigate the affect of temperature of a connecting pipe, as a representative of different ambient temperature against a solar cooling machine performance. The experiment will show in what condition a solar cooling is going to have a better cooling result. The data used in this case was taken experimentally and conducted using a solar cooling machine equipped with temperature measurement units such as thermocouple logger. For cold ambient temperature, in adsorption process, refrigerant vapour flows to the generator through the connecting pipe cooled by water and kept steady. The results show that the COP, heat and mass transfer of adsorbent bed of the system in the adsorption process on a warm condition are better than in a cold environment. In the warm condition the COP system is 0.24, the heat transfer rate is 0.06 Â°C/minute, and the mass transfer rate is 1.09 ml/minute. Whereas, in the cold condition the COP system is 0.23, the heat transfer rate is 0.05 Â°C/minute, and the mass transfer rate is 1.04 ml/minute.Â